Shared pathogenicity features and sequences between EBV, SARS-CoV-2, and HLA class I molecule-binding motifs with a potential role in autoimmunity - Adıgüzel, Yekbun; Mahroum, Naim; Muller, Sylviane; Blank, Miri; Halpert, Gilad; Shoenfeld, Yehuda (Springer, 2023)
Epstein-Barr virus (EBV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are extraordinary in their ability to activate autoimmunity as well as to induce diverse autoimmune diseases. Here we reviewed the current knowledge on their relation. Further, we suggested that molecular mimicry could be a possible common mechanism of autoimmunity induction in the susceptible individuals infected with SARS-CoV-2. Molecular mimicry between SARS-CoV-2 and human proteins, and EBV and human proteins, are present. Besides, relation of the pathogenicity associated with both coronavirus diseases and EBV supports the notion. As a proof-of-the-concept, we investigated 8mer sequences with shared 5mers of SARS-CoV-2, EBV, and human proteins, which were predicted as epitopes binding to the same human leukocyte antigen (HLA) supertype representatives. We identified significant number of human peptide sequences with predicted-affinities to the HLA-A*02:01 allele. Rest of the peptide sequences had predicted-affinities to the HLA-A*02:01, HLA-B*40:01, HLA-B*27:05, HLA-A*01:01, and HLA-B*39:01 alleles. Carriers of these serotypes can be under a higher risk of autoimmune response induction upon getting infected, through molecular mimicry-based mechanisms common to SARS-CoV-2 and EBV infections. We additionally reviewed established associations of the identified proteins with the EBV-related pathogenicity and with the autoimmune diseases.
Keywords: COVID-19; Post-COVID; Autoimmune Disease; MHC; Infectious Molecular Mimicry